Решите уравнение х-2/6 +х/2=5х-2/9 5+2х/3=х-3/5+х+5/2 3(х+1)/8+2(5х)/3=16-13х/12 5(7-2х)/3-4х-2/9=х-19/2    

Решите уравнение х-2/6 +х/2=5х-2/9 5+2х/3=х-3/5+х+5/2 3(х+1)/8+2(5х)/3=16-13х/12 5(7-2х)/3-4х-2/9=х-19/2    
Гость
Ответ(ы) на вопрос:
Гость
x-2/6+x/2 = 5x-2/9 5x-x-x/2 = 2/9-2/6 7/2x = -1/9 x = -1/9*2/7 x = -2/63 5+2x/3=x-3/5+x+5/2 2x-2/3x = 5+3/5-5/2 4/3x = 31/10 x = 31/10*3/4 x = 93/10 3(x+1)/8+2(5x)/3=16-13x/12     ×24 9(x+1)+16*5x = 384-26x 9x+9+80x = 384-26x 89x+26x = 384-9 115x = 375 x = 375/115 = 75/23 = 3 6/23 5(7-2x)/3-4x-2/9=x-19/2    ×18 30(7-2x)-72x-4 = 18x-171 210-60x-72x-4 = 18x-171 18x+60x+72x = 210-4+171 150x = 377 x = 377/150 = 2 77/150
Не нашли ответ?
Ответить на вопрос
Похожие вопросы